Synergistic Activity of the HSP90 Inhibitor Ganetespib With Lapatinib Reverses Acquired Lapatinib Resistance in HER2-Positive Breast Cancer Cells - Ye, Min; Huang, Wei; Liu, Rui; Kong, Yingli; Liu, Yang; Chen, Xiaole; Xu, Jianhua (Frontiers in Pharmacology, 2021)
Lapatinib is an approved EGFR and HER2 tyrosine kinase inhibitor by FDA for HER2-positive breast cancer patients. However, its therapeutic efficacy is limited by primary or acquired resistance. In the present study, we established the acquired lapatinib-resistant breast cancer cells, and investigated the antitumor activity of the second-generation HSP90 inhibitor ganetespib associated with lapatinib in the lapatinib-sensitive and resistant cells. The combination treatment showed synergistic inhibition in the HER and downstream PI3K/Akt and Ras/MEK/ERK pathway, and enhanced induction of early apoptotic cell death and G1 arrest in both parent and lapatinib-resistant cells in vitro. The joint administration by ganetespib and lapatinib depleted the aberrant nuclear transcription factors STAT3 and its mediated downstream cell cylcle and apoptosis-related pathways, which were probably involved in the lapatinib resistance of HER2-positive breast cancer cells. In conjunctive with the augmented inhibition of tumor growth in both SKBR3 and SKBR3-L xenograft compared to monotherapy, our data provide a sound preclinical basis for the combination of lapatinib and ganetespib in the refractory HER2-positive breast cancer treatment.